United States Supreme Court Justices Biographical Data, 1789-1958 - Schmidhauser, John R. ([Verlag nicht ermittelbar], 1984)
This study contains biographical data on the 92 Supreme Court justices appointed between 1789 and 1958. Potter C. Stewart, appointed in 1958, was the last justice to be included in the study. The study recorded personal data such as place of birth, education, political as well as nonpolitical occupation, legal and judicial experience, age at the time of Supreme Court appointment, ethnic background, and religious affiliation. Other background information on each justice includes party identification, reputation as a frequent dissenter, and the state from which he was appointed. Various aspects of family background such as social and economic status, paternal occupation, and familial traditions of judicial service were also explored.